Analisa Perilaku Aman Pekerja UPT Balai Yasa dengan Pendekatan Model Perilaku ABC - Julaikah Julaikah (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2019)
Background: The ABC behavioral model was used to understand why some behaviors can occur and become an effective way to improve the expected behaviors because in ABC behavioral model there are consequences that can be used to motivate the frequency of expected behaviors to increase. The result of Balai Yasa Yogyakarta clinical report documents observation was known that 80% accident incident reported caused by unsafe action. The usage of PPE is the spearhead of accident prevention applied in Balai Yasa because other risks control measures such as elimination, substitution, and modification cannot be applied because all the control efforts are related to the work process. Some efforts to control risk by administration has been implemented but not maximized due to continuous socialization efforts besides the safety talks cannot be implemented.Objective: To understand safety behavior of UPT Balai Yasa Workers especially personal protective equipment (PPE) utilization used ABC Approach. Methods: This research used qualitative approach with descriptive research type. The sampling technique used was purposive sampling. The research subjects were 15 people. The data analysis used content analysis.Results: Activator (A) which plays a role in the usage of PPE was the role of management, knowledge, awareness, and attitudes of workers. Both external and internal activators were interrelated and cannot stand on their own to be able to generate the safe behaviors at work. Consequences (C) in the use of PPE in UPT Balai Yasa Yogyakarta has not run well, that make the less role in the formation of workers behavior. Some reasons workers did not use PPE during work were: (a) PPE was unavailable, (b) PPE was uncomfortable, (c) lack of strict consequences, (d) low worker awareness of the importance of using PPE.Conclusion: The formation of obedience behaviors of the PPE usage by production workers need synergy between the activator element(A) and consistency of implementation of consequences (C). Keywords: Safety Behavior, ABC Approach, Behavior Based Safety, PPE utilization.